Therapy with boceprevir or telaprevir in HIV/hepatitis C virus co-infected patients to treat recurrence of hepatitis C virus infection after liver transplantation. (2nd January 2015) - Antonini, Teresa Maria; Furlan, Valerie; Teicher, Elina; Haim-Boukobza, Stephanie; Sebagh, Mylene; Coilly, Audrey; Bonhomme-Faivre, Laurence; Roque-Afonso, Anne-Marie; Vittecoq, Daniel; Samuel, Didier; Taburet, Anne-Marie; Duclos-Vallée, Jean Charles
<x xml:space="preserve">Abstract</x> Objective: Severe hepatitis C virus (HCV) recurrence affects post-transplant survival in HIV/HCV co-infected patients. This article describes the results of triple anti-HCV therapy with boceprevir or telaprevir in seven HIV/HCV co-infected patients following liver transplantation. Methods: All patients had severe HCV recurrence [fibrosis stage ≥F2 or acute hepatitis ≥A2 (n = 5) or fibrosing cholestatic hepatitis (n = 2)] associated with genotype 1a (n = 4) or 1b (n = 3). Patients were treated with Peg-interferon/ribavirin and boceprevir (n = 2) or telaprevir (n = 5) immediately (n = 3) or after a 4-week lead-in phase (n = 4). Immunosuppression included either cyclosporine (n = 5) or tacrolimus (n = 2). Prior to introducing telaprevir, combined antiretroviral therapy was switched in one patient to prevent drug–drug interactions. Results: At 24 weeks after the end of treatment, sustained virological response was observed in 60% (3/5) of the patients treated with telaprevir; no responders were observed in the boceprevir group. Triple anti-HCV therapy was prematurely discontinued in six patients [treatment failure (n = 2), infection (n = 2), acute rejection (n = 1) and myocardial infarction (n = 1)]. Anaemia occurred in all patients, requiring erythropoietin, ribavirin dose reduction and red blood cell transfusions in five patients. Average cyclosporine doses were reduced by 50–84% after telaprevir initiation and by 33% after boceprevir initiation. Tacrolimus doses were reduced by 95% with telaprevir. Conclusion: Our data suggest that in HIV/HCV co-infected patients, triple anti-HCV therapy with telaprevir greatly improved efficacy despite poor tolerability. Significant decreases in cyclosporine or tacrolimus doses are necessary prior to introduction of boceprevir or telaprevir. Close monitoring is essential to prevent drug–drug interactions among antiretroviral therapy, immunosuppressive agents and anti-HCV therapy.